Effect of time of pre-irrigation and tillage practices on wheat (Triticum aestivum) under pigeonpea (Cajanus cajan) - wheat cropping sequence - SINGH, Y P; SINGH, DHARVENDRA; TOMAR, S S; GUPTA, RAJ K (The Indian Journal of Agricultural Sciences, 2026)
A field experiment on wheat (Triticum aestivum L.) under pigeonpea (Cajanus cajan (L.) Millsp) wheat cropping sequence was carried out in rabi season of 2010-11 and 2011-12 to evaluate time of pre-irrigation such as before and after harvest of pigeonpea and different tillage practices, viz. zero tillage (ZT), minimum tillage (MT), conventional tillage (CT) sowing methods on growth, yield, economics and soil properties on sandy loam soil. Pre-irrigation before harvest of pigeonpea significantly influenced the growth parameters, yield, net profit, benefit cost (B : C) ratio, energy input, output, use-efficiency and energy productivity as compared to pre-irrigation after harvest of pigeonpea. Similarly, growth parameters, yield, net return, B:C ratio, energy output, use-efficiency and productivity of energy were significantly influenced by ZT sowing method compared with CT, whereas non-significant difference in growth parameters and yield between MT and CT treatment was observed. Maximum energy input was noticed in CT followed by MT and ZT. The increase in grain and straw yields by 5.32% and 5.94%, respectively, was observed with ZT over CT. Maximum cost of production was observed with CT as compared to MT and ZT. With ZT the maximum of Ruppes 3 760/ha was saved followed by MT (Ruppes 1 490/ha) as compared to CT. Total water-used by wheat was significantly higher in CT (43.57 cm) as compared to ZT (40.66 cm), whereas maximum water use efficiency with ZT was 108.1 kg followed by CT (96.9 kg) and MT (95.2 kg). The water use efficiency for CT and MT was at par. Pre-irrigation before harvesting of pigeonpea significantly improved water-use efficiency (105.1 kg) as compared to pre-irrigation after harvest of pigeonpea (95.0 kg). After harvest of wheat, organic carbon and infiltration rate were significantly influenced under ZT followed by MT and CT. Lowest bulk density was noticed in surface soil (0 to 15 cm depth) with ZT as compared to other methods of tillage, while there was slight increase in bulk density of sub-surface soil (15-30 cm depth) in all the treatments..